Salmonella Typhimurium Infection Leads to Colonization of the Mouse Brain and Is Not Completely Cured With Antibiotics - Chaudhuri, Debalina; Roy Chowdhury, Atish; Biswas, Biswendu; Chakravortty, Dipshikha (Frontiers in Microbiology, 2018)
Salmonella systemic infections claim thousands of lives worldwide even today. Certain cases of Salmonella infection can lead to an infection in the brain culminating in meningitis and associated neurological abnormalities. Multiple reports have indicated neurological manifestations in patients suffering from typhoid fever during the course of infection and afterwards. While the meanderings of Salmonella systemic infections are fairly well studied, the flow of events in the brain is very poorly understood. We investigated the colonization of various brain parts by Salmonella in mice. It was observed that the bacterium is frequently able to invade various brain parts in mice. Selected mutants namely deletion mutants of key proteins encoded by the Salmonella pathogenicity islands 1 and 2 and ompA gene were also used to decipher the roles of specific genes in establishing an infection in the brain. Our results suggest roles for the Salmonella pathogenicity island 1 and outer membrane protein A gene in enabling blood-brain barrier penetration by the pathogen. We further investigated behavioural abnormalities in infected mice and used an antibiotic treatment regime in an attempt to reverse the same. Results show some mice still display behavioural abnormalities and a high bacterial burden in brain despite clearance from spleen and liver. Overall, our study provides novel insights into S.Typhimurium’s capacity to invade the mouse brain and the effectiveness of antibiotic treatment on behavioural manifestations due to infection. These observations could have important implications in understanding reported neurological manifestations in typhoid patients.